Enabling Private Investment in 5G Connectivity in Emerging Markets : An Assessment of Challenges and Policy Options - Houngbonon, Georges V. (International Finance Corporation, Washington, DC, 2021)
This note proposes a high-level framework to assess challenges and policy options to enabling private sector-led investment in 5G connectivity in emerging markets. 5G is the latest mobile network technology and it has the potential to provide high-speed Internet connectivity and enable digital transformation across multiple sectors of an economy. The proposed framework leverages industry data to articulate the digital divide and benchmark the enabling environment for 5G connectivity in emerging markets. The note concludes with recommendations on policy options and business strategies, drawing from early experiences in advanced markets and major opportunities and challenges in emerging markets.